1938
DOI: 10.1128/jb.36.5.467-479.1938
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Metabolism of the R and S Variants of Lactobacillus plantarum (Orla-Jensen)

Abstract: The extreme variability in fermentation reactions of lactobacilli is well known. Weiss and Rettger (1934), Curran, Rogers andWhittier (1933), andHowitt (1930) have ably reviewed this subject.The alterations in fermentative reactions have seldom however been clearly correlated with colonial dissociation. Roos (1927) isolated from one strain of Lactobacillus acidophilus three distinct fermentative and colonial types. Hadley, Bunting and Delves (1930) found that R variants obtained from S strains of oral aciduric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1939
1939
1954
1954

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
(22 reference statements)
1
3
0
Order By: Relevance
“…From these experiments it appears that the "degeneration phenomenon" described is a further example of the well known S -> R variation. A similar connection between metabolic changes and S -* R variation apparent in our experiments has been described previously, notably by Tracy (1938) in the case of Lactobacillus plantarum.…”
Section: Discussionsupporting
confidence: 90%
“…From these experiments it appears that the "degeneration phenomenon" described is a further example of the well known S -> R variation. A similar connection between metabolic changes and S -* R variation apparent in our experiments has been described previously, notably by Tracy (1938) in the case of Lactobacillus plantarum.…”
Section: Discussionsupporting
confidence: 90%
“…Kopeloff (1934) and Raney and Kopeloff (1934) observed that dissociation from rough to smooth was common with L. acidophilus. Tracy (1938) was able to obtain rough and smooth types of colonies from a culture of Lactobacillus plantarum in which the dissociation was smooth to rough. The rough culture was very stable but the smooth culture remained stable only if transfers in glucose broth were made once or twice a week.…”
mentioning
confidence: 99%
“…For example, Harrison (1942) found that in certain lactobacilli loss of the type-specific polysaccharide was accompanied by loss of ability to ferment mannitol and sorbitol. Tracy (1938) demonstrated that the S -+ R change in Lactobacillus plantarum was correlated with loss of ability by the R strain to form acid from various sugars, and in acquisition by the R form of an ability to grow in carbohydrate-free media.…”
Section: Resultsmentioning
confidence: 99%